The literary hero Sherlock Holmes, his relationship with Asperger syndrome and ICT’s role in literacy - Manola, Maria; Vouglanis, Taxiarchis; Maniou, Fotini; Driga, Anna Maria (Eximia, 2023)
Asperger syndrome is a severe developmental disorder characterized by major difficulties in social interaction and restricted and unusual patterns of interest and behavior. Sherlock Holmes has, through this study, been shown to be a high-functioning Asperger's individual, which can make his symptoms a little less obvious at times. His love of objective logic, his deep and persistent need for analysis, his unusual interests and mannerisms, his disregard for social norms, and his extraordinary passion are hallmarks of the syndrome. He is also occasionally stubborn when people don't understand him or his needs.